EFFECT OF PARTICLE SIZE DAN ANGLE OF IMPACT IN SLURRY EROSION ON MEDIUM CARBON STEEL USING LIQUID JET IMPINGEMENT METHOD - NARIZKY B.P. TAMPUBOLON (NIM : 13706022); Dosen Pembimbing : Dr. Ir. Bambang Widyanto, EZRA
Erosion occurs as the result of materials interaction with fluid having significant velocity as its environment. Erosion on materials can produce many kind of damage including weight loss, change of appearance, even loss of thickness on workpiece due to loss of material on the surface. The existence of solid particle in fluids will add effect on erosion rate. In this research, liquid jet impingement method will be used to study the effect of erosion by slurry containing silica sand suspension in water, on medium carbon steel. This method considered suitable for representing in situ condition due to continuous fluid flow. Size of the particle used in this research is 75-149 μm and 210-297 μm. Angle of impact used in this research is 90Ã‚Âº and 45Ã‚Âº. The result shows higher loss of thickness and mass occurs in 210-297 μm particle size due to higher mass of the particle giving it higher kinetics energy. While 45Ã‚Âº angle of impact also shows higher loss of thickness on surface profile, although with lower weight loss. Lower weight loss gained as the result of material loss concentrated only in horizontal axis of the specimen and lower angle of impact will give lower decrease in slurries traveling velocity as the slurry changing direction.